Algorithms utilizing peripheral blood hematopoietic progenitor cell counts in lieu of some CD34+ cell counts predict successful peripheral blood stem cell collections with substantial time and cost savings. (5th October 2016) - Steussy, B. W.; Capper, M.; Krasowski, M. D.; Rosenthal, N. S.; Schlueter, A. J.
Abstract : Background and Objectives: Hematopoietic progenitor cell (HPC) counts from Sysmex hematology analyzers have been shown to correlate with peripheral blood (PB) CD34+ cell counts by flow cytometry. Algorithms utilizing HPC counts to guide stem cell collections have been proposed but rarely tested. This study describes the development and validation of algorithms utilizing HPC and PB CD34+ cell counts to predict adequate peripheral blood stem cell (PBSC) collections for chemomobilized and cytokine‐mobilized individuals. Materials and Methods: Utilizing a test set of 83 PB samples from chemomobilized or cytokine‐mobilized PBSC collection patients, PB CD34+ counts were correlated with HPC counts and a receiver operating characteristic curve was constructed. Cut‐offs of ≤0·5 HPC/ μ l and ≥7 HPC/ μ l were established to maximize sensitivity and specificity for using HPC to predict PB CD34+ ≥ 10 cells/ μ l. These cut‐offs were subsequently validated using a separate prospective validation set of 88 HPC/CD34+ cell sample pairs. Results: Using the algorithms, all patients in the prospective validation data set achieved adequate collections of ≥1 × 10 6 CD34+ cells/kg, and a 67% reduction in the number of CD34+ cell counts performed was achieved. This lead to a direct cost savings of at least 18 700 USD over a 21‐month period (88% reduction in direct costs). Conclusion: Use of the algorithms provides significant time and cost savings for the laboratory while accurately predicting (i) timing of PBSC collections to obtain adequate CD34+ product yields for chemomobilized patients and (ii) when to administer plerixafor to cytokine‐mobilized patients to improve the likelihood of achieving adequate collections.